Starting designs for broadband chirped mirrors - Pervak, V.Yu.; Telyatnikov, V.O.; Pervak, Yu.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
The chirped mirror (CM) is one of the key elements in ultrafast optics. We
investigate a problem of a CM designing. The series of starting designs for broadband
CM are reported. The appropriate starting design can significantly simplify a problem of
design searching, and improved a performance of a final solution. The acceptable
performance of CM was achieved by optimization one of the proposed starting design.
The achieved design has comparable performance in comparison with the best design
which was realized up to now.